Optimizing Granulated Palm Sugar (Arenga pinnata (Wurmb) Merr.) And Sodium Chloride Formulation to Improve Physicochemical Quality And Sensory Acceptance Of Pork Dendeng - Rotinsulu, Merri D.; Sakul, Syalom; Sorongan, Syalom (Sam Ratulangi University, 2026)
This study evaluated the effects of different combinations of granulated palm sugar (gula semut) and sodium chloride (NaCl) on the physicochemical and sensory quality of pork dendeng. A completely randomized design (CRD) with three treatments and five replications (3×5) was applied. Treatments were formulated on a meat-weight basis (w/w): A1 (2.5% gula semut + 7.5% NaCl), A2 (5.0% gula semut + 5.0% NaCl), and A3 (7.5% gula semut + 2.5% NaCl). For each replication, 200 g pork ham was ground (5 mm plate), mixed with the assigned ingredients, rested at 4 °C for 12–24 h, and dried in a cabinet oven at 80 °C for 11 h. Moisture content (AOAC 950.46), pH, water-holding capacity (WHC; press method), and cooking loss were measured. Sensory acceptance (color, aroma, texture, and taste) was evaluated by 25 untrained panelists using a five-point hedonic scale. Data were analyzed using one-way ANOVA followed by BNJ (Tukey’s HSD) at P < 0.05. The formulation significantly affected WHC and cooking loss. Treatment A2 produced the highest WHC (19.51%) and the lowest cooking loss (40.90%), indicating improved water retention and thermal yield compared with A1 and A3 (P < 0.05). pH values (6.61–6.69) and hedonic scores for all sensory attributes did not differ significantly among treatments (P > 0.05). Overall, a balanced gula semut–NaCl formulation (5%:5%) is recommended to enhance pork dendeng processing performance while maintaining acceptable sensory quality. Keywords: cooking loss; gula semut; pork dendeng; sodium chloride; water-holding capacity